2016
DOI: 10.1016/j.jpowsour.2016.09.083
|View full text |Cite
|
Sign up to set email alerts
|

A method for the fast estimation of a battery entropy-variation high-resolution curve – Application on a commercial LiFePO4/graphite cell

Abstract: The entropy-variation of a battery is responsible for heat generation or consumption during operation and its prior measurement is mandatory for developing a thermal model. It is generally done through the potentiometric method which is considered as a reference. However, it requires several days or weeks to get a look-up table with a 5 or 10 % SoC (State of Charge) resolution. In this study, a calorimetric method based on the inversion of a thermal model is proposed for the fast estimation of a nearly continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…There is a lack in the literature for using the calorimeter method directly to determine the entropic coefficient. The exception is Damay et al [29] who used the calorimeter as the direct measurement to determine the entropy profile with various current levels. In [29] the entropy effect is calculated from the subtraction of the charging heat and discharging heat, therefore only the average entropy profile of charge and discharge can be obtained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a lack in the literature for using the calorimeter method directly to determine the entropic coefficient. The exception is Damay et al [29] who used the calorimeter as the direct measurement to determine the entropy profile with various current levels. In [29] the entropy effect is calculated from the subtraction of the charging heat and discharging heat, therefore only the average entropy profile of charge and discharge can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The exception is Damay et al [29] who used the calorimeter as the direct measurement to determine the entropy profile with various current levels. In [29] the entropy effect is calculated from the subtraction of the charging heat and discharging heat, therefore only the average entropy profile of charge and discharge can be obtained. Overall the calorimetric method is a relatively fast method and it gives a continuously entropy profile for the whole SoC range.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of heat depends on the discharging rate. Thus, in battery engineering practice, it is often suggested that the heat flow P follows the Joule-Lenz law that together with the Ohm law has the form P = I 2 R (I is the current and R is the battery's internal resistance), for instance, see works; [1][2][3][4] however, we have not found either theoretical or experimental proof of applicability of this formula. In case of the lithium-ion battery, the heat flow at high discharge current can overheat the battery up to unsafe conditions, and there is no need to repeat how widely lithiumion batteries are distributed in modern consumer and special devices.…”
mentioning
confidence: 78%
“…Damay et al proposed the advanced calorimetric method along with the improvement plans of the existing calorimetric method. According to the authors, it is possible to accurately obtain entropyvariation as a function of SOC by creating experimental conditions of high cell temperatures and low current-rates [18]. Geifes et al extracted the entropic heat coefficient from the pulse relaxation measurement and refined them through least squares estimation.…”
Section: Introductionmentioning
confidence: 99%